Mulaprasada (main shrine) of the Jain Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the mulaprasada (main shrine) of the Jain Temple. The temple elevation has a vedibandha (basal mouldings) with minimal ornamentation, followed by a jangha (wall) which has figural sculptures and an intricately carved multi-spired shikhara (superstructure).